2003
DOI: 10.1161/01.cir.0000070022.78747.1b
|View full text |Cite
|
Sign up to set email alerts
|

Different Differentiation Kinetics of Vascular Progenitor Cells in Primate and Mouse Embryonic Stem Cells

Abstract: Background— We demonstrated that vascular endothelial growth factor receptor 2 (VEGF-R2)-positive cells derived from mouse embryonic stem (ES) cells can differentiate into both endothelial cells and mural cells to suffice as vascular progenitor cells (VPCs). Here we examined whether VPCs occur in primate ES cells and investigated the differences in VPC differentiation kinetics between primate and mouse ES cells. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 15 publications
6
57
0
Order By: Relevance
“…In our study, the expression of FLK1 was upregulated on day 6, before hematopoietic development. This result is consistent with the recent report on vascular progenitor cell differentiation from cynomolgus monkey ES cells onto OP9 stromal cells (Sone et al, 2003). Furthermore, we observed that exogenous VEGF also enhances the development of vascular endothelial cadherin-positive endothelial colonies under the same culture conditions (K.U., T.H.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the expression of FLK1 was upregulated on day 6, before hematopoietic development. This result is consistent with the recent report on vascular progenitor cell differentiation from cynomolgus monkey ES cells onto OP9 stromal cells (Sone et al, 2003). Furthermore, we observed that exogenous VEGF also enhances the development of vascular endothelial cadherin-positive endothelial colonies under the same culture conditions (K.U., T.H.…”
Section: Discussionsupporting
confidence: 93%
“…Its expression was also documented in undifferentiated ES cells (63)(64)(65)(66). Our present findings indicate that VEGFR-2 is expressed in ES cells and that its expression is induced by hypoxia via a HIF-1␣-dependent pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, ES cells could be feasible as a novel cell source for therapeutic angiogenesis. Recently, we were able to clarify the differentiation process from human ES cells to mature vascular cells (Figure 1) [Sone et al 2007[Sone et al , 2003]. Unlike mouse ES cells, undifferentiated human ES cells already express VEGFR-2, but after differentiation, a VEGFR-2-positive but tumor rejection antigen 1-60 (TRA1-60; undifferentiated marker)-negative population emerged.…”
Section: Es Cell-derived Ecsmentioning
confidence: 99%